Simulation of transmission line filters for GaAs MMIC - Naca, Cecilia L.; Santos, Ralph L. (2010)
There is a wide study of different filter implementations to keep up with the increasing demand for miniaturization and multi-functionality in wireless communication systems. Designing RF filters with small size at high frequencies and at lower costs is a challenge. This project aimed to study the feasibility of transmission line based filters for Gallium Arsenide (GaAs) Monolithic Microwave Integrated Circuit (MMIC) applications operating in the ISM band based on NIPs fabrication process. The low pass and high pass filter topologies were implemented using stepped impedance, optimized high pass and commensurate line while the band pass filter topology were implemented using combline and interdigital method. Simulation and characterization was done using a computer aided design tool. The results of the different filter topologies and implementations were analyzed based on their return loss, attenuation and operating frequencies. The physical dimension of the filters was taken into account since one of the advantages of MMIC technology in communication systems was its small size.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Electric filters; Electric filters, Bandpass; Monolithic microwave integrated circuits